CARACTERIZAÇÃO DE PAINÉS COMPÓSITOS DE CIMENTO PORTLAND E FIBRAS DE CURAUÁ (ANANAS ERECTIFOLIUS) - Bilcati, Gessica; Trianoski, Rosilani; Lengowski, Elaine Cristina; Matoski, Adalberto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The objective of this work is characterize the performance of the Fiber of Amazon Ananas erectifolius as reinforcement in the production of portland cement panels. The study methodology was developed from the manufacture of composite cement Portland and fibers with varying types of treatments performed, seeking the best property of materials. Were performed in a cold water treatment for 24 hours immersion, hot water immersion for 6 hours at 60 ° C and sodium hydroxide immersion with concentration at 1% for 2 hours. The fibers treated with sodium hydroxide produced a panel with weak mechanical properties when compared to other treatments. The physical properties treatment provided positive influence in the absorption of water and in the thickness swelling.